Mucosal relapse of visceral leishmaniasis in a child treated with anti-TNFα. (April 2015) - Jeziorski, E.; Dereure, J.; Mac Bullen, G.; Blanchet, C.; Ludwig, C.; Costes, V.; Rodière, M.
Highlights: Tumour necrosis factor (TNF) is an important component of the immune response against leishmaniasis infection. A patient on anti-TNF therapy may develop visceral leishmaniasis. Mucosal forms of Leishmania infantum infection in an endemic area are rare, but exist. These are favoured by immunosuppression. Visceral and mucosal are possible disseminated forms of human leishmaniasis due to L. infantum, similar to canine leishmaniasis due to L. infantum and like human leishmaniasis in HIV-infected people. Summary: Visceral leishmaniasis is an enzootic parasitosis present across the Mediterranean Basin. Some consider it an opportunistic parasite. We report the case of a girl treated with anti-tumour necrosis factor alpha (anti-TNFα) for juvenile idiopathic arthritis who had previously presented with visceral leishmaniasis. Two and a half years later, she presented a tumour-like mass in the nasal mucous membrane caused by Leishmania parasites. Leishmania infantum is classically responsible for visceral leishmaniasis, but pure mucocutaneous leishmaniasis has also been described. To our knowledge, this is the first observation of a recurrence of visceral leishmaniasis in the mucocutaneous form. The occurrence of atypical forms and presentations in those on anti-TNF therapy should be considered.